2020
DOI: 10.22500/8202028458
|View full text |Cite
|
Sign up to set email alerts
|

Rural Livelihood Vulnerability and Resilience: a Typology Drawn from Case Studies of Small-Scale Farmers and Fishermen in Indonesia

Abstract: Various studies on rural household livelihood systems have been carried out in Indonesia to explain the level of household livelihood vulnerability in both farming and fishing communities. The livelihood of small-scale farmers and fishermen is usually vulnerable due to climate and non-climate pressure. This desk study compares the results of studies on livelihood vulnerability from various theses, dissertations and scientific journal articles with a similar topic of study. A case study analysis is used to figu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…By employing the framework of the SLA, further comprehensive studies (Bhandari, 2013;Liu and Liu, 2016;Hua et al, 2017;Pour et al, 2018) have confirmed the great importance of various types of livelihood capital to household livelihood strategy decisions. In addition to within-household driving factors, some studies place more emphasis on the influencing factors of shocks from social-economic-ecological changes (Dharmawan and Manig, 2000;Schraven, 2010;Poudel and Shaw, 2015), policy and institutional environments (Chen et al, 2013;Zhen et al, 2014) and tourism development (Mbaiwa, 2011;Kheiri and Nasihatkon, 2016). These help us design the analytical framework.…”
Section: The Impact Of Farmland Transfer Participation On Farmers' Li...mentioning
confidence: 99%
“…By employing the framework of the SLA, further comprehensive studies (Bhandari, 2013;Liu and Liu, 2016;Hua et al, 2017;Pour et al, 2018) have confirmed the great importance of various types of livelihood capital to household livelihood strategy decisions. In addition to within-household driving factors, some studies place more emphasis on the influencing factors of shocks from social-economic-ecological changes (Dharmawan and Manig, 2000;Schraven, 2010;Poudel and Shaw, 2015), policy and institutional environments (Chen et al, 2013;Zhen et al, 2014) and tourism development (Mbaiwa, 2011;Kheiri and Nasihatkon, 2016). These help us design the analytical framework.…”
Section: The Impact Of Farmland Transfer Participation On Farmers' Li...mentioning
confidence: 99%
“…The implication is that many PAC men and women do not know about the explicit strategy. The livelihoods of rural communities cannot be generalized because they are interrelated [64,68,69].…”
Section: Gender Perspective In Pac Livelihood Recoverymentioning
confidence: 99%
“…An individual household's adaptive capacities determine climatic vulnerability. The impact of climate change is also determined by the magnitude and extent of households affected (Dharmawan & Nissa 2020). Such is the case of flooding, landslides, and earth movements in Kenya during the heavy rains in April, May, and even June; however, not all families were adversely affected, while others displace amid the COVID-19 scare.…”
Section: The Scarcity Of Food Commoditiesmentioning
confidence: 99%